Swallowing and aspiration during sleep in patients with obstructive sleep apnea versus control individuals. Issue 4 (15th February 2022) - Kohno, Akane; Kohno, Masaki; Ohkoshi, Shogo
Abstract: Study Objectives: There are only a few reports on voluntary swallowing during sleep; therefore, this study aimed to propose a method for observing voluntary swallowing during sleep using polysomnography. The frequency of voluntary swallowing during sleep and the factors related to swallowing and aspiration during sleep were investigated. Methods: Polysomnography records of 20 control subjects and 60 patients with obstructive sleep apnea (OSA) (mild, moderate, and severe groups; n = 20 each) were collected. Simultaneous increases in the electromyographic potentials of the submental and masseter muscles, termed coactivation, and declining oronasal airflow (SA) were extracted as "swallowing." The cough reflex that occurred during sleep was extracted as "aspiration." The frequency of swallowing events was compared among the different OSA severity groups. Subsequently, a multivariate regression analysis was performed. Results: The average frequency of coactivation with SA in control subjects was 4.1 events/h and that without SA was 1.7 events/h. These frequencies increased with the severity of OSA during non-REM sleep. The distance of the hyoid to the Frankfurt plane was associated with the frequency of coactivation with (β = 0.298, p = 0.017) as well as without SA (β = 0.271, p = 0.038). The frequency of coactivation without SA was associated with aspiration (B = 0.192, p = 0.042). Conclusions: Our data provide new insights into the relationship between swallowing and aspiration during sleep. We found that the longer the distance from the hyoid bone to the Frankfurt plane, the higher the coactivation without SA, which could lead to aspiration during sleep. Clinical Trials: Retrospective observational study of swallowing during sleep in obstructive sleep apnea patients using polysomnography, https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000050460, UMIN000044187.